Leptin and steroid hormone responses to exercise in adolescent female runners over a 7-week season - Kraemer, R. R.; Acevedo, E. O.; Synovitz, L. B.; Hebert, E. P.; Gimpel, T.; Castracane, V. D. (European Journal of Applied Physiology, 2001)
The purpose of the study was to investigate the responses of leptin and steroid hormones to maximal exercise in adolescent female runners over a competitive season. Seven adolescent female distance runners completed three testing trials during weeks 1, 4 and 7 of their high-school track season. Blood samples were collected before and after a discontinuous graded exercise test to exhaustion (GXT) for each trial. Tests were administered during the subjects' normal training time (3:30 p.m.-5:00 p.m.). Compared to week 1, peak O2 uptake rose significantly during the season and was 10% and 7% higher at weeks 4 and 7, respectively. Levels of dehydroepiandrosterone (DHEA), dehydroepiandrosterone sulfate (DHEAS), cortisol, testosterone, and leptin increased significantly in response to the graded exercise tests. Testosterone levels were also changed over the course of the study. Resting testosterone levels and testosterone responses to exercise in weeks 4 and 7 were both higher than in week 1. Resting concentrations and acute increases of the other hormones were not changed over the season. It appears, therefore, that DHEA, DHEAS, cortisol, testosterone and leptin concentrations increase in response to running in adolescent female runners. Data also suggest that training and/or maturation increases resting testosterone concentrations and testosterone responses to running in adolescent female runners during a training season.